Oxylipin production and novel ascospore release mechanisms in the yeast Dipodascus - Van Heerden, Ane (University of the Free State, 2006)
Certain ascomycetous yeasts produce "lubricated" 3-hydroxy (3-OH) oxylipin-coated, micron-scale sexual spores in a variety of shapes, sizes, colors and sometimes with nano-scale surface ornamentations. In past literature, these oxylipin-coated ornamentations are only mentioned for use in classification and no thought was given to their possible purpose or function. These 3-OH oxylipins were found to be associated with the sheathed ascospores of some species representing the genus Dipodascus. However, these compounds have not yet been studied in detail in this genus. In addition, no thought was given to the mystery behind the release mechanics of sheathed ascospores from enclosing bottle-shaped asci and the role of these 3-OH oxylipins during dispersal. Therefore, it became the aim in this study to determine 3-OH oxylipin structure, distribution and function in D. albidus UOFS Y-1445T and D. geniculatus UOFS Y-1144 and to reveal the secrets behind the release mechanics of sheathed ascospores from bottle-shaped asci in these two species. Using electron microscopy, confocal laser scanning microscopy, gas chromatography-mass spectrometry (GC-MS) and digital live imaging, the release mechanisms of ascospores of various lengths from bottle-shaped asci, and produced by different yeasts, are compared in this study. It was found that Dipodascus albidus produces oval ascospores that are surrounded by compressible, oxylipin-coated sheaths enabling ascospores to slide past each other when forced by turgor pressure and by possible sheath contractions towards the narrowing ascus-neck. Usually elongated ascospores, as found in Dipodascopsis uninucleata var. uninuc/eata, are linked by means of oxylipin-coated interlocked hooked ridges on the surfaces of neighbouring ascospores, thereby keeping them aligned while being pushed towards the ascus-tip by turgor pressure. Interestingly, it was uncovered in this study that Dipodascus geniculatus produce elongated, oxylipin-coated sheathed ascospores that are effectively released from bottle-shaped asci without alignment. This is possible because the ascus neck and opening have the same diameter as the length of the ascospore, thus allowing the ascospores to turn sideways without blocking the ascus upon release. Interestingly, it was found that increased concentrations of acetylsalicylic acid (ASA), inhibit both ascospore release and 3-OH oxylipin production in these yeasts, thereby implicating this oxylipin in sexual reproduction. Using GC-MS analysis, the oxylipin was characterized as a3-OH metabolite. The same mass spectrum, implicating the presence of the same 3-0H oxylipin structure, was found to be present in other Dipodascus species. This implicates that this 3-0H metabolite might be conserved on genus level.

Sommige askomisete giste produseer mikron-skaal geslagtelike spore in 'n verskeidenheid van vorms, grootes, kleure en somtyds met nano-skaal oppervlak omamentasies wat met "smerende" 3-hidroksie- (3-OH)-oksielipiene bedek is. In literatuur word daar slegs melding gemaak van hierdie oksielipienbedekte ornamentasies vir klassifikasiedoeleindes maar geen aandag word aan hul moontlike doelof funksie geskenk nie. Die 3-OH-oksielipiene word met die skedes, wat die askospore in sommige spesies van die genus Dipodascus omring, geassosieer. Hierdie komponente is egter nog nie in besonderheid in hierdie genus bestudeer nie. Geen aandag is ook aan die misterie van die vrylatingsmeganika van skede-omringde askospore vanuit geslote bottelvormige aski geskenk of die rol wat 3-OH-oksielipiene tydens verspreiding speel nie. Die doelstellings van hierdie studie is dus om die 3-OH oksielipienstruktuur, verspreiding en funksie in D. albidus UOFS Y- 1445T en D. geniculatus UOFS Y-1144 te bepaal en om die geheime agter die vrylatingsmeganika van skede-omringde askospore vanuit bottelvormige aski in the twee genoemde spesies te verklaar. In hierdie studie word m.b.V. elektron-mikroskopie, konfokalelaserskandeermikroskopie, gaschromatografiemassaspektrometrie (GC-MS) en digitale uitbeelding, die vrystellingsmeganismes van askospore, geproduseer deur verskillende giste, van verskillende lengtes vanuit bottelvormige aski vergelyk. Daar is bevind dat Dipodascus albidus ovaalvormige askospore, omring deur saampersbare, oksielipienbedekte skedes, produseer. Deur turgordruk en vergroting van die skede, word hierdie askospore na die vemoude bottelnek gedruk deurdat die oksielipien-bedekte skedes die askospore verby mekaar laat skuur. Gewoonlik word verlengde askospore, soos in Dipodascopsis uninucleata var. uninucleata gevind, aan mekaar verbind deur oppervlakhoeke wat soos ratte aan mekaar gekoppel is, om te verseker dat die askospore in gelid bly soos dit na die askuspunt gedruk word. Interessant genoeg, is in hierdie studie ontdek dat Dipodascus geniculatus verlengde askospore met oksielipien-bedekte skedes produseer wat effektief vanuit bottlevorminge aski vrygestel word sonder dat hulle in gelid geplaas word. Dit is moontlik deurdat die askusnek en askusopening dieselfde deursnit as die lengte van die askospoor het. Dus kan die askospore skuins draai tydens vrystelling sonder om die askus te blokkeer. Met die byvoeging van 'n 3-0H-oksielipieninhibeerder, asetielsalisiensuur (ASS), is hoofsaaklik die geslagtelike fase, meer spesifiek, askospoorvrystelling geïnhibeer, asook 3-OHoksielipienproduksie. Dit bevestig dat die oksielipiene met die geslagtelike voorplantingstrukture geassosieer word. Met die gebruik van GC-MS, is bepaal dat die oksielipien 'n 3-OH metaboliet is. Dieselfde massaspektrum, wat op die teenwoordigheid van dieselfde 3-OH oksielipien struktuur dui, is ook in ander Dipodascus spesies gevind. Dit impliseer dat hierdie 3-OH metaboliet dalk op genus vlak gekonserveerd is.
Dissertation (M.Sc. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2006
Keywords: Alignment; Ascospore; Dipodascus albidus; Dipodascus geniculatus; Elongated ascospores; 3-Hydroxy oxylipin; Release mechanism; Yeast; Lipids; Dipodascus